Educação de surdos, pedagogia de projetos em escola com proposta bilíngue: realidades e perspectivas - Silva, Nathália Marcélia Gonçalves (2024)
Given the concrete sociocultural and educational reality that involves people with deafness, bilingual school education for the deaf has had a legal apparatus since 2005. The legislation specifically aimed at deaf people includes the Brazilian Sign Language (Libras), in the bilingual school proposal for deaf people, as a first language (L1) and Portuguese identified as a second language (L2) in written form. Signing deaf students (Libras users) benefit in this context from the recognition of their singularities. The general objective of this research is to analyze and problematize the conceptions and practice of Project Pedagogy in Bilingual Education for the Deaf, identifying the realities and perspectives with propositions that aim for meaningful learning. The research has as its locus the São Paulo Educational Institute (IESP) of the Division of Education and Rehabilitation of Communication Disorders (DERDIC), academically linked to the Pontifical Catholic University of São Paulo (PUC-SP). The research methodology is characterized by a qualitative approach, with procedures such as bibliographical study, document analysis and semi-structured interviews with teachers from Elementary School II (6th to 9th year). The theoretical contributions refer to school education and social coexistence, Freire (1997;2023), Arroyo (2013), Sacristán (2013), Ponce (2016) and Silveira and Ramos (2020). Regarding the school education of deaf people, Skliar (1998), Strobel (2008;2009), Vieira (2017), Campello (2018) and Pereira (2014;2022). The basis for Active Methodologies follows the conceptualization of Bacich; Moran (2018). Project Pedagogy has Hernández (2004;2011;2017) as its main reference, approaches to the sociopolitical and cultural context are based on the authors Santos (2006) and Bauman (2007) and teacher training is based on Feldmann; Masetto (2017). The delimitation of the methodology uses Gil (2002;2008) and Chizzotti (2003), among other authors. The results identified that teachers from the perspective of bilingual education for the deaf seek to develop different pedagogical practices in order to guarantee the right to learning for deaf students. Project Pedagogy in this context contributes to imagery work, autonomous and with a deaf protagonism, favoring the development of criticality and reflective positions guided by democratic values in social coexistence